'My dream is that I share the bed with only one man': Perceptions and practices of premarital sex among Catholic women in Belgium. (March 2022) - Huygens, Eline
Drawing on qualitative research with Catholic women who are active in the Church in Belgium, this article sets out to analyse how these women negotiate and manage premarital sexuality. I map their practices, experiences, and strategies, and explore how they make sense of religious and secular norms regarding premarital sexuality. By using two notions as theoretical frameworks, namely religious agency and growth ethics, I argue that combining both can lead to a fertile approach to yielding new insights into the field of religion and sexuality. In so doing, I demonstrate that although not all my interlocutors refrain from sexual relations before marriage, they develop personal sexual ethics, which are distinctly informed by Catholic understandings.